Coagulation profiles and platelet parameters among preeclampsia, eclampsia, and normotensive pregnant women attending Comprehensive Specialized Hospital maternity wards, Northwest Ethiopia. - Nigusie Alemu; Bisrat Birke Teketelew; Sintayehu Admas; Lyusira Marelgn; Yalweayker Eyayu; Berhanu Woldu (PLoS ONE)
Background Hypertensive disorders of pregnancy affect about 10% of all pregnant women worldwide. A variety of hematological abnormalities may occur in women with pregnancy-induced hypertension. Thus, we aimed to compare coagulation profiles and platelet parameters among preeclampsia, eclampsia, and normotensive pregnant women in Northwest Ethiopia. Method A comparative cross-sectional study was conducted at University of Gondar and Felegehiwot Comprehensive Specialized Hospital, maternity wards from June 20 to November 15, 2024. A total of 180 participants were recruited using the convenience sampling technique. Socio-demographic and clinical data were collected using a structured questionnaire and participants' medical records. Eight milliliters of blood specimens were collected from each study participant. Coagulation profiles and platelet parameters were measured using a Genrui coagulation analyzer and an automated Mindray BC-5150 hematological analyzer, respectively. Data were entered into epi-data version 4.6.0.6 and exported to the SPSS version 26 software for analysis. Descriptive data were presented using tables and frequencies. One-way ANOVA and Kruskal-Wallis tests were used for normally distributed and skewed data, respectively. A p < 0.05 was considered statistically significant. Results A total of 180 pregnant women were enrolled/included in this study. The median PT and aPTT showed prolongation in preeclampsia and eclampsia patients, as compared to normotensive pregnant women, indicating a significant difference (p < 0.001) and (P = 0.002) respectively. The mean ± SD of mean platelet volume and PDW showed higher values in preeclampsia and eclampsia patients, as compared to normotensive pregnant women, demonstrating both a significant difference (P < 0.001). On the other hand, the mean platelet count in preeclampsia and eclampsia patients, were lower than in normotensive pregnant women, with a significant difference (p < 0.001). Conclusion and recommendations In this study, alteration of coagulation and platelet parameters were observed in preeclampsia and eclampsia pregnant womens compared to normotensive controls. Thus, a routine laboratory test of coagulation and platelet parameters for pregnant women with preeclampsia and eclampsia could be applicable to reduce the risk of coaglation and platelet abnormalities.